Central Bank independence and economic performance in Caucasus and Central Asian Countries - Rizvanoghlu, Islam; Nagac, Abdulkadir (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
This paper explores the association of both central bank independence (CBI) and financial market development with the economic performance of Turkey together with six former centrally planned former Soviet Union countries located in Caucasus and Central Asia (CCA countries). First, we construct a legal independence index (LVAW) for central banks. Then, we analyze the relationship between central bank independence and macroeconomic variables. Our findings suggest that there is a positive correlation between central bank independence and GDP growth, whereas the sign of correlation between CBI and GDP deflator is negative. Besides, the economies with higher level of financial deepening are also associated with high CBI.